Psychological factors and visual fatigue in working with video display terminals. - Mocci F; Serra A; Corrias GA; Mocci, F; Serra, A; Corrias, G A (Occupational & Environmental Medicine, 2001)
Objectives: To examine the part played by psychological factors in complaints about visual health reported by banking officers who work at video display terminals (VDTs).Methods: Out of a population of 385 bank workers, a group of 212 subjects without organic visual disturbances (as determined by ophthalmological examination) who share a work environment and job duties was selected. Three questionnaires were administered to these subjects: (a) the NIOSH job stress questionnaire; (b) a questionnaire investigating subjective discomfort related to environmental and lighting conditions of the workplace; (c) a questionnaire on the existence of oculovisual disturbances. Correlation and multiple regression analyses were performed to examine for the presence of predictors of asthenopia.Results: Social support, group conflict, self esteem, work satisfaction, and underuse of skills were found to be predictors of visual complaints; social support played a part also as a moderating factor in the stress and strain model; this model accounted for 30% of the variance. Subjective environmental factors, although in some cases significantly correlated with asthenopia, were not found to be strong predictors of the symptoms.Conclusions: Some part of the complaints about visual health reported by VDT workers are likely indirect expressions of psychological discomfort related to working conditions.